From Hashtags to Code-Switching: A Critical Discourse Analysis of Language Evolution on Social Media - Moses Adeleke Adeoye (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2026)
Language has always adapted to cultural and technological shifts, but the rise of social media has accelerated this evolution, reshaping how individuals communicate, construct identities, and negotiate power. With billions of users worldwide, platforms such as Twitter, Instagram, and Facebook have become key arenas where linguistic innovations and cultural expressions intersect with ideological struggles. This research investigates how social media discourse contributes to language evolution, focusing on three interrelated dimensions: linguistic innovation, identity construction, and power relations. Specifically, it examines how features such as hashtags, emojis, memes, and code-switching function as tools for creativity, belonging, and ideological framing. A mixed-methods design was employed, combining quantitative content analysis with Critical Discourse Analysis (CDA). A purposive sample of 500 posts, collected across major platforms, was coded for linguistic features and analysed in terms of how discourse reflected innovation, constructed identities, and reinforced or challenged power structures. The findings reveal that 72% of posts used abbreviations and acronyms, while 65% incorporated emojis, underscoring a trend toward brevity and emotional expressiveness. Code-switching appeared in 50% of posts, signalling hybrid cultural identities, and 75% of posts included cultural references that reinforced belonging. Hashtags emerged as powerful discursive tools: 68% of posts employed them for resistance and advocacy, while 45% perpetuated stereotypes, illustrating the dual role of social media in empowerment and marginalisation. The research concludes that social media is not only a site of linguistic creativity but also a space where identities are negotiated and ideologies contested. By integrating CDA with quantitative analysis, this research contributes a holistic framework for understanding language evolution in digital contexts, offering insights relevant to sociolinguists, educators, policymakers, and digital communities.